Motoric Stimulation Related to Fine Motoric Development on Child - Mira Triharini; Retnayu Pradanie; Dwiyanti Permata Sari (Jurnal Ners, 2009)
Introduction: Motor developmental stimulation is an activity undertaken to stimulate the children basic skills and so they can grow and develop optimally. Children who obtain a direct stimulus will grow faster than who get less stimulus. Mother’s behavior of stimulation is very important for children, it is considering as the basic needs of children and it must be fulfilled. Providing good stimulation could optimize fine motor development in children. The purpose of this study was to analyze mother’s behavior about motor stimulation with fine motor development in toddler age 4-5 years old.Method: Design have been  used in this study was cross sectional. Population were mothers and their toddler in Group A of Dharma Wanita Persatuan Driyorejo Gresik Preschool. Sample were 51 respondents recruited by using purposive sampling technique according to inclusion and exclusion criteria. The independent variable was mother’s behavior about motor stimulation whereas dependent variable was fine motor development in toddler. The data were collected using questionnaire and conducting observation on fine motor development based on Denver Development Screening Test (DDST). Data then analyzed using Spearman Rho (r) test to find relation between mother’s behaviors about stimulation motor on their toddler fine motor development.Result: Results  of this study showed that there were correlations between mother’s knowledge and fine motor development in toddler (p=0.000), between mother’s attitude and fine motor development in toddler (p=0.000), and between mother’s actions and fine motor development in toddler (p=0.000).Conclusion: In sort study found that there were relation between fine motor development and mother’s behavior. Discussion: Therefore mother’s behavior needed to be improved. Further research about stimulation motor and fine motor development aspects in toddler is required.